THE MEITEI TRADITIONAL POLITICAL PRACTICES - Soyaphy Khangrah, Dr. Jacob Luiram (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Manipur state is one of the India’s gateways to south-east Asia and it attracted immigrants from the east and the west throughout centuries. The Meitei society is not a homogenous groups, it was gradually formed after they migrated to the present habitat. The evolution of Meitei society does not happen in a day; it stretches from centuries and became successful in consolidating themselves into strong Meitei community in the 15th century. According to Cheitharol Kumbaba, the royal chronicles of the kings of Manipur, the antiquity of the institution of kingship in Manipur can be traced back to 33A.D. The chronicles record that Nongda Lairen Pakhangba was coronated to the throne of Kangla. The Meitei who had established their kingdom in the valley claimed that their areas of administration extended up to the Kabow valley in the Burma. The Meitei society who had attained different level of political organization in historical period was drawn into several controversies regarding their political status after the British left Manipur.